2014
DOI: 10.4103/2141-9248.139327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of work related musculoskeletal disorders among physicians, surgeons and dentists: A comparative study

Abstract: Background:Work related musculoskeletal disorders (MSDs) are one of the common occupational hazards among health care providers.Aim:The objective of this study was to evaluate MSDs in terms of perception of pain experienced by physicians, surgeons and dental surgeons during professional work.Subjects and Methods:The study was conducted with 100 physicians practicing either modern or alternative medicine, 100 surgeons of various specialties and 100 dental surgeons. Self-reporting work related questionnaire on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
7
51
2
1
Order By: Relevance
“…Out of 160 (100.0%) health care professionals 109 (68.1%) had musculoskeletal pain or discomfort in the last 12 months and 51 (31.9%) had not, and it was also found that 57 (61.3%) doctors and 52 (77.6%) nurses had musculoskeletal pain or discomfort in the last 12 months, which was quite similar to the study findings [12] , where the prevalence and risk factors for low back pain among a variety of Turkish hospital workers, including nurses, physicians, physical therapists, technicians, secretaries, and hospital aides, in which the highest prevalence was reported by nurses (77.1%).This study result showed the prevalence of work-related musculoskeletal disorders in different body region in the last 12 months, where more than 1 site involvement 46 (42.2%) followed by neck 19 (17.4%), shoulder 15 (13.8%), lower back 13 (11.9%), hips 8 (7.3%), hand/fingers 5(4.6%) which was close to the study. [13,14] In a comparative study [15] more than 1 site involvement of MSDs among dentists were showed 35.0%, which was consistent with the present study findings. Among 109 (100.0%) health care professionals who had musculoskeletal pain or discomfort, almost three fourth 78(71.5%) mentioned that pain not affecting their job, where as 31(28.4%) mentioned that pain affecting their job.…”
Section: Discussionsupporting
confidence: 82%
“…Out of 160 (100.0%) health care professionals 109 (68.1%) had musculoskeletal pain or discomfort in the last 12 months and 51 (31.9%) had not, and it was also found that 57 (61.3%) doctors and 52 (77.6%) nurses had musculoskeletal pain or discomfort in the last 12 months, which was quite similar to the study findings [12] , where the prevalence and risk factors for low back pain among a variety of Turkish hospital workers, including nurses, physicians, physical therapists, technicians, secretaries, and hospital aides, in which the highest prevalence was reported by nurses (77.1%).This study result showed the prevalence of work-related musculoskeletal disorders in different body region in the last 12 months, where more than 1 site involvement 46 (42.2%) followed by neck 19 (17.4%), shoulder 15 (13.8%), lower back 13 (11.9%), hips 8 (7.3%), hand/fingers 5(4.6%) which was close to the study. [13,14] In a comparative study [15] more than 1 site involvement of MSDs among dentists were showed 35.0%, which was consistent with the present study findings. Among 109 (100.0%) health care professionals who had musculoskeletal pain or discomfort, almost three fourth 78(71.5%) mentioned that pain not affecting their job, where as 31(28.4%) mentioned that pain affecting their job.…”
Section: Discussionsupporting
confidence: 82%
“…MSDs in more than one site was significantly higher among dentists (73.2%) than physicians (50%) ( Table 2) which was in accordance with Rambabu and Suneetha, (2014) who found that 31.6% of physicians and 60% of dentists with MSDs had musculoskeletal problems in more than one site.…”
Section: Discussionsupporting
confidence: 80%
“…[26] The rate of lower back pain in our study was 22.8% among all respondents. It has been reported that standing without the freedom to sit increases the risk of experiencing a lower back pain.…”
Section: Discussionmentioning
confidence: 76%